Africa and the Middle East: the Politics of Asymmetry - Olusola, Ojo (Obafemi Awolowo University Press, 2012)
The operation of the contemporary international system involves a very complex web, of relationships among states and the other actors 'in the system. The scope, intensity, regularity and tile nature of each state's relationships With and, within the system are a function of many variables, Geography, the quantity and quality of resources both human and natural technological development, shared history and shared values go a long way in determining each state's stake in the system, as well as the degree to which these stakes are pursued and the strategies for pursuing them. And because resources and capabilities are not evenly 'shared by the members of the international system, there are disparities in the amount of influence members wield in the, system. These' disparities create a relationship of dependency between the 'have' and the .have-nets' which oftentimes develop into an asymmetrical relationship: They follow the basis of the categorization of states into super, big, middle-ranked and small powers. However, irrespective of their status, states are dependent on other ,members of the system in one way or the other as no, state has enough resources to satisfy its needs. In other words, in order to achieve their objectives - whether defined in terms of political, economic, cultural, social or technological - states have to interact with one another.' The need to satisfy these interests has led members of tile system to devise strategies for collaboration and for the management of conflict, In all of tile relationships, a basic tenet of interaction is tile equality of members. In reality, however, this is more legal than political: relations are often lopsided, hierarchical, unequal or asymmetrical. In a relationship of asymmetry, tile extent to which the component members of the system share in the conditions and concerns of tile system 'vary widely, even to tile point that one can question whether a system actually exists. In this situation, it is often difficult to discern interests their could be clearly considered mutual. Each component unit would 'have about it a unique feature or set of features which separate ill important ways. Its inquests from those of any other state or the system considered as a whole. Clear lines of division would be necessary and jealously guarded insofar as these unique interests are concerned. Consequently. the dominant 'states pursue their goals with little or no difference to the Interests and concerns .of the other members of the system. (Tarlton, 1965). '